Sensitivity analysis of singular vectors of cover matrix as basis of steganography algorithm, that steady to lossy compression - Кобозєва, Алла Анатоліївна; Мельник, Маргарита Олександрівна (Ukrainian Information Security Research Journal, 2013)
The problem of creating steganography algorithm, that steady to lossy compression with significant ratios remains unsolved to date, although lossy compression is one of the most common attacks on stegano messages. Traditional approach in this field is using frequency domain container, while ensuring the reliability of perception formed stegano message, guaranteed to provide resistance to compression of steganography algorithms only with minor coefficients. In the frequency domain is fundamentally impossible to solve the problem. Early has shown that the properties of any steganography algorithm determined by the localization of disturbances occurred during stegano transformation, formal parameters that make up a complete set - singular values and singular vectors of a matrix container. This paper covers the analysis of image’s singular vectors sensitivity to compression, selected the least sensitive vectors. It is shown that the left and right singular vectors corresponding to the maximum singular values are sign-insensitive. They are close to the optimal n-vector of R8-space with any disturbances. These results are the basis for steganographic techniques and algorithms that are resistant to compression with large coefficients